Diseases of Desmodium species - A review - Lenné, Jillian M.; Stanton, J.M. (1990)
Fungal pathogens representing 36 genera and over 70 species, one bacterium, mycoplasma-like-organisms, at least six viruses, five races of root-knot nematodes and six other nematodes have been recorded on 18 Desmodium species of agronomic interest throughout tropical regions. Although limited information precludes a definitive discussion of the relative importance of many diseases, two fungal diseases — Synchytrium desmodii and Phanerochaeta salmonicolor — causing wart and pink disease, respectively, of Desmodium ovalifolium and several nematode pathogens including races of the root-knot nematodes Meloidogyne arenaria, M. hapla, M. incognita and M. javanica of Desmodium species and stem gall nematode Pterotylenchus cecidogenus of D. ovalifolium are presently regarded as important pathogens. Awareness of the range and distribution of fungal pathogens recorded on Desmodium species as well as the existence of potentially seed-borne bacteria and potyviruses is regarded as essential for preventing global transmission of these pathogens and serious disease problems in the future. This is the first time that the great diversity of information available on diseases of Desmodium species has been summarised. It should provide a useful reference for many tropical pasture scientists.